PERLAWANAN PETANI RENGAS TERHADAP PTPN VII DI OGAN ILIR SUMATERASELATAN - Mohammad Syawaludin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
This research has a title the Repertoire of Farmer’s Movement: a Study about the Opposition of Farmers against PTPN VII Unit Usaha Cinta Manis in the village of Rengas, the sub-district of Payamaran, the regency of Ogan Ilir, South Sumatera. This research focuses on the change of the movement and the relation of the effort’s goal achievement. The form of the opposition movement in Rengas is developing the repertoire of opposition movement and committing the change of the action to interacton be contention period. Through the analysis of periodical, this research can describe the progress from the fist process of the structure development and the expansion of the movement structure until the action of the movement structure’s change after the massive reclamation is committed. The method of this research uses qualitative approach of case studies and cause. This approach intends to rationalism, social reality, politic, and culture. Besides, the choosing of single case study method is research strategy that helps the researcher to investigate a program, phenomenon, activity, process, and individual group accurately. The case is limited by the time and the type where the researcher can accumulate the information completely and measurably.